Development of Bale Mangrove Ecotourism Potential Through Improving English Literacy and Communication Skills in Jerowaru Village, East Lombok - Junaidi, Abdul Majid; Hamidy, Rasyid Ridho; Subhan, Mohammad (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
This community service program aims to develop the potential of Bale Mangrove ecotourism in Jerowaru Village, East Lombok, by improving the English literacy and communication skills of tourism managers. Given that Jerowaru Village has great ecotourism potential, especially in terms of environmental conservation and nature tourism, English communication skills are an important skill to improve the quality of tourism services and attract foreign tourists. Community service activities are carried out through a series of training and mentoring focused on improving English speaking skills and introducing tourism terms in English. The methods used include a participatory approach, in which the local community, especially youth and Bale Mangrove managers, play an active role in the entire series of activities. The results of this program show a significant increase in the English communication skills of participants, which is expected to support sustainable ecotourism development. In addition, improving English literacy also contributes to the preparation of more attractive and professional ecotourism promotional materials. The main obstacles faced are limited training time and limited access to more varied learning resources. In conclusion, the development of Bale Mangrove ecotourism through improving English literacy and communication skills has a positive impact on local tourism potential and community welfare. It is recommended that there be a more in-depth follow-up program and support from the local government to strengthen the sustainable tourism ecosystem in Jerowaru Village.